Improving parents and teachers' knowledge about household organic waste composting - Ika Wahyuning Widiarti; Aulia Syifa Ardiati (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Most people still underestimate organic waste, so this waste always ends up in the Landfill. How to process organic waste into compost has been widely informed. However, community participation in self-managing organic waste has still not increased. Therefore, this community service activity aims to provide knowledge about household organic waste processing. The methods used in this program include lectures and discussions, demonstrations, and pre-post tests for evaluation. This program was carried out on November 30, 2019, with participants' targets, namely parents and teachers of Permata Hatiku School. This program was carried out on November 30, 2019, with participants' targets, namely parents and teachers of Permata Hatiku School. The various composting methods presented in the lectures include the composter bin method, Takamura, bio-pore, and jugangan (holes) in the ground. In addition, it also explained the basic principles of composting and how to make a bio-starter. The demonstration was carried out by practicing how to make a natural bio-starter known as local microorganisms (MOL) from rotten fruits. Composting was demonstrated by using the composter bin method with kitchen waste. The participant well-received the program materials. An increase in the post-test score marks it compared to the pre-test score.